A QSAR Study on a Series of Pyrrole Derivatives Acting as Lymphocyte- Specific Kinase (Lck) Inhibitors - Anwer, Zaihra; P. Gupta, Satya (Medicinal Chemistry, 2012)
A quantitative structure-activity relationship (QSAR) study has been made on a novel series of pyrrole derivatives acting as lymphocyte-specific kinase (Lck) inhibitors. The Lck inhibition activity of compounds is found to be significantly correlated with their molar volume (MV) and surface tension (ST) and the hydrophobic constant of one of their substituents. Both the molar properties MV and ST of the compounds are found to have the negative effect but the hydrophobic property of R2-substituen is found to have the positive effect. This leads to suggest that the bulky molecules and the those with high surface tension will not be advantageous to the Lck inhibition, rather their R2-substituent with hydrophobic property will be conducive to the activity.
Keywords: pyrrole derivatives